2018
DOI: 10.1111/hae.13546
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes from prophylactic or episodic treatment of haemophilia A: A systematic review

Abstract: This systematic review confirmed that the benefits of prophylactic treatment on short-term outcomes translate to broader long-term clinical, humanistic and economic benefits. Better harmonization of data collection and outcome assessments across both registries and clinical studies is needed to allow for effective comparisons across studies and across data sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 36 publications
2
30
0
1
Order By: Relevance
“…Therefore, this treatment should be continued lifelong. 1,4,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][34][35][36] However, data on adult patients benefitting from prophylaxis are limited.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, this treatment should be continued lifelong. 1,4,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][34][35][36] However, data on adult patients benefitting from prophylaxis are limited.…”
Section: Discussionmentioning
confidence: 99%
“…recommendation and strengthen comparable results of previous studies revealing the superior benefit of prophylaxis compared to on-demand treatment in adolescents and adults with HA. 9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26]34 This prospective study is the longest NIS of a single FVIII concentrate reported so far in which treatment data were collected from the routine treatment of HA patients. 32 In a broad range of patients with severe as well as non-severe HA, covering all age groups up to 88 years, long-term prophylaxis with a pdFVIII concentrate reduced the ABR remarkably, in some cases down to zero.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
See 2 more Smart Citations
“…3 Cross-sectional data on health-related quality of life and other patient-reported outcomes (PROs) in clinical trials in haemophilia are available. 4 However, there is a lack of real-world data exploring the relationships between longitudinal changes of PROs, clinical outcomes and treatment patterns/products across different countries.…”
Section: Introductionmentioning
confidence: 99%